Genotyping by Sequencing Advancements in Barley - Rajendran, Nirmal Raj; Qureshi, Naeela; Pourkheirandish, Mohammad (Frontiers in Plant Science, 2022)
Barley is one of the ideal crops to study cereal genetics due to its close relationship with wheat and its diploid ancestral genome. It has the potential to play a crucial role in tackling challenges posed by climatic change threatening global food security. Genetic variations in the traits of interest are vital for any crop improvement program to succeed. DNA markers have been widely used to tap into these variations in populations. With the advancements in next-generation sequencing, breeders could access DNA variation among different lines, with the most popular single nucleotide polymorphisms (SNPs). However, the barley genome complexity came up with numerous challenges in sequence read alignment and computational errors during whole genome sequencing (WGS) due to its large genome size (5.5GB) and high proportion of repetitive elements (80%). Furthermore, its cost is still high, hindering the wider application of WGS. Genotyping-by-sequencing (GBS) protocols based on restriction enzymes and target enrichment aid SNP discovery by reducing the genome complexity and providing a cost-effective option. In general, GBS has opened up new horizons in the field of plant breeding and genetics. Though a reliable alternative to WGS, GBS is not devoid of computational difficulties and GBS specific pipelines are currently available to overcome these challenges. Moreover, a robust design for GBS can facilitate the imputation at WGS level for crops with high linkage disequilibrium. Complete exploitation of GBS advancements will pave the way to a better understanding of genetics and offer opportunities for crop improvement both in barley and its close relatives.